Job Satisfaction among the Nurses of Makueni District Hospital, Kenya - Anthony wambua Mathulu; Benard Wambua Mbithi (Intelektual Pustaka Media Utama, 2016)
The purpose of the study was to evaluate the level of job satisfaction among the nurses of Makueni District Hospital. This was necessitated by the high nurse staff turnover from the facility and a myriad of complains from various departments. The study was a cross sectional descriptive survey involving about 50 nurses that was carried out between 15 and 19th July 2013. The study employed mixed method approach. Tests of significance were through use of Chi-square, Fishers exact test and logistic regression. The key results were that overall job satisfaction was low (36%). There were significant relationships between job satisfaction and cordial relationship with the nurse manager (c2 12.131 df 4 p=0.016<0.05. Logistic regression p=0.018<0.05). The plans to quit the hospital and work elsewhere indicates a relationship with job satisfaction (c2 12.749 df 4 p=0.013<0.05). The findings of this study suggest that there is no enabling working environment for the nurses and this could be a barrier to service delivery in the Hospital. These findings suggest that the Nurse Managers should build up effective relationship with the staff and other departments and should identify negative working conditions which affect staff and appropriately delegate authority to them.